State of the international wine market in 2022: New market trends for wines require new strategies - Rafael del Rey; Simone Loose (Wine Economics and Policy, 2023)
The objective of this discussion paper is to provide an overview of the state of the global wine sector in 2022 and discuss the effects of recent events on the wine trade's development. First, long-term trends in the global consumption and production of wine and the development of the international wine trade are discussed. The growth trend of global wine consumption ceased in 2008, but the last decade in the global wine trade has been characterised by stagnant volumes but increasing values driven by premiumisation. Several recent events have affected the volume or composition of the global wine trade: the recovery of the wine trade after Covid-19, global cost increases and inflation, the shift of Chinese wine consumption and the effect of the Russian invasion of Ukraine on Russian wine imports. The paper closes with an outlook on how underlying long-term trends might affect the strategies that successful wine business can employ in the future and suggests future areas of research in the wine business and economics.
Keywords: 330; global wine trade; wine consumption trends; inflation; COVID; industry strategies; RussiaLess